Analisis Pengaruh Kepuasan dan Motivasi Kerja terhadap Kinerja Penjual pada PT Indomobil Trada Nasional - Taufan, Sonny; Mustofa, Ismail; Mustofa, Mustofa; Purwojatmiko, B. Handoko (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
Job satisfaction and work motivation are identified as critical factors that can influence an individual's level of performance in a competitive work environment such as the automotive industry. This research aims to analyze the influence of job satisfaction and work motivation on the performance of branded vehicle sellers at PT Indomobil Trada Nasional – KIA Kelapa Gading. This research uses a quantitative approach with survey methods. Data was collected through a questionnaire distributed to KIA vehicle sellers at PT Indomobil Trada Nasional. Respondents in this research were sellers who were actively working. The collected data was then analyzed using regression analysis techniques to measure the relationship between the independent variables (job satisfaction and work motivation) and the dependent variable (seller performance). It is hoped that the results of this research will provide deeper insight into the factors that influence the performance of KIA sellers in these automotive companies. The results of the regression analysis will show the extent to which job satisfaction and work motivation are able to predict sales performance. These findings will provide valuable input for the management of PT Indomobil Trada Nasional in formulating strategies to improve sales performance through increasing job satisfaction and motivation. It is hoped that this research will contribute to the human resource management literature and provide practical guidance for companies in the automotive industry or other similar sectors. In addition, this research can also be a basis for further research on the influence of other factors that can influence individual performance in different work contexts.